2018
DOI: 10.1016/j.epsl.2018.04.062
|View full text |Cite
|
Sign up to set email alerts
|

The geophysics, geology and mechanics of slow fault slip

Abstract: Modern geodetic and seismologic observations describe the behavior of fault slip over a vast range of spatial and temporal scales. Slip at sub-seismogenic speeds is evident from top to bottom of lithospheric faults and plays an important role throughout the earthquake cycle. Where earthquakes and tremor accompany slow slip, they help illuminate the spatiotemporal evolution of fault slip. Geophysical subsurface imaging and geologic field studies provide information about suitable environments of slow slip. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
326
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(337 citation statements)
references
References 243 publications
(107 reference statements)
9
326
1
1
Order By: Relevance
“…We now know that some faults are locked up to the surface while others slip aseismically down to seismogenic depth (e.g., Cetin et al, ; Jolivet et al, ). Finally, growing evidence suggests the nucleation, propagation, and arrest of seismic rupture are mediated by slow slip, which in turn directly affects the seismic hazard in tectonically active regions (e.g., Avouac, ; Bürgmann, ; Obara & Kato, ).…”
Section: Slow Slip Is Ubiquitousmentioning
confidence: 99%
“…We now know that some faults are locked up to the surface while others slip aseismically down to seismogenic depth (e.g., Cetin et al, ; Jolivet et al, ). Finally, growing evidence suggests the nucleation, propagation, and arrest of seismic rupture are mediated by slow slip, which in turn directly affects the seismic hazard in tectonically active regions (e.g., Avouac, ; Bürgmann, ; Obara & Kato, ).…”
Section: Slow Slip Is Ubiquitousmentioning
confidence: 99%
“…Aseismic slip can occur with various temporal behaviors: it can be steady (e.g., Fialko, 2006;Motagh et al, 2007), as observed during the interseismic period, or transient (e.g., Hayes et al, 2014), either triggered by a major earthquake and decaying with time (postseismic relaxation known as afterslip, e.g., Lienkaemper et al, 2001) or spontaneously generated by processes still poorly understood. Frictional properties, fault geometry and lithology, as well as pore fluid pressure variations were proposed to explain creep behavior (Avouac, 2015;Bürgmann, 2018). For example, the presence of clay-rich gouges and high fluid pressure appear as key factors for the presence of creep (Carpenter et al, 2011, Kaduri et al, 2017, 2018.…”
Section: Fault Creep and Seismic Potentialmentioning
confidence: 99%
“…Frictional properties, fault geometry and lithology, as well as pore fluid pressure variations were proposed to explain creep behavior (Avouac, 2015;Bürgmann, 2018). For example, the presence of clay-rich gouges and high fluid pressure appear as key factors for the presence of creep (Carpenter et al, 2011, Kaduri et al, 2017, 2018. Recent development and widespread use of advanced space-based techniques, particularly interferometric synthetic aperture radar (InSAR), has revealed that steady or transient surface creep behavior along major continental faults is more common than previously thought.…”
Section: Fault Creep and Seismic Potentialmentioning
confidence: 99%
“…Stress perturbations from a mainshock rupture can trigger spontaneous or delayed SSEs (over hours to months; e.g., Hayes et al, 2014;Hirose et al, 2012;Rolandone et al, 2018), which release stress that had built up during the previous inter-SSE interval (Bürgmann, 2018), and can also trigger transient creep (Lienkaemper et al, 1997;Wei et al, 2015) or modulate surface creep rate (Xu et al, 2018). In general, dynamic triggering of SSEs remains a rare phenomenon, and only a few cases are documented (Araki et al, 2017;Itaba & Ando, 2011;Wallace et al, 2017;Zigone et al, 2012).…”
Section: Introductionmentioning
confidence: 99%